2020
DOI: 10.1002/cbdv.202000462
|View full text |Cite
|
Sign up to set email alerts
|

Composition and Larvicidal Activity of the Oil of Dizygostemon riparius (Plantaginaceae), a New Aromatic Species Occurring in Maranhão, Brazil

Abstract: Dizygostemon riparius (Plantaginaceae) is a new aromatic herbaceous species occurring in Maranhão State, Brazil. It is used as flavorings to remove domestic animal parasites and preventing mosquitoes. GC and GC/MS were used to analyze its essential oil, and a larvicidal bioassay was performed against Aedes albopictus larvae, a vector of arboviruses in Brazil. endo-Fenchyl acetate, endo-fenchol, (E)-caryophyllene, and caryophyllene oxide were the oil's primary constituents, totalizing 88.0 %. The two morphotype… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 27 publications
(43 reference statements)
2
6
0
Order By: Relevance
“…The yield in the extraction of the essential oils was of 1.5% for both studied species, similar to the observed in other studies (BRANDÃO et al, 2020;OLIVEIRA et al, 2011).…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…The yield in the extraction of the essential oils was of 1.5% for both studied species, similar to the observed in other studies (BRANDÃO et al, 2020;OLIVEIRA et al, 2011).…”
Section: Resultssupporting
confidence: 90%
“…During the evaluations was evidenced a sharp leaf fall from the fourth day in both treatments with essential oils, being of greater intensity in the treatments with the D. riparius oil. According to Brandão et al (2020), no other essential oil with high fenchil and fenchol acetate content was previously found in the literature. This can be a factor that justifies the high phytotoxicity caused in seedlings and fruits, when treated with D. riparius essential oil.…”
Section: Antifungal Potential Of Essential Oils Frommentioning
confidence: 96%
See 1 more Smart Citation
“…The analysis of the mean contents and standard deviations of the constituents present in the D. riparius oils in the circadian study (see Figure 8) showed that the formed Group I was The yield and composition of the essential oil of Dizygostemon riparius were previously reported, with an oil content of 1.5 % and exhibiting endo-fenchyl acetate (48.0 %), endo-fenchol (35.0 %), (E)-caryophyllene (6.8 %), and caryophyllene oxide (3.3 %) as its main constituents. [10] Newly, the ethyl acetate and methanol extracts from D. riparius showed the presence of polymethoxyflavones and coumarins, such as isorhamnetin-3galactoside-7-rhamnoside, 3',5-dihydroxy-4',6,7-trimethoxyflavone, and 5,7-dihydroxy-3-(3-hydroxy-4,5-dimethoxyphenyl)-6-methoxy-4-benzopyrone. [17] The oil of D. riparius has a refreshing and pleasant scent, similar to that of lemon and camphor, due to the presence of endo-fenchyl acetate and endo-fenchol, with a percentual of 83 %.…”
Section: Multivariate Analysis Of D Riparius Oils In the Circadian Studymentioning
confidence: 99%
“…Its leaves and thin stems have a refreshing and pleasant aroma, are used as a food flavoring, control parasites of domestic animals, and prevent mosquitoes. [9,10] In Brazil, the representative genera of Plantaginaceae are Achetaria Cham. & Schltdl., Dizygostemon (Benth.)…”
Section: Introductionmentioning
confidence: 99%